Arisan Sebagai Modal Sosial Pedagangdi Pasar Sentral Kota Kendari - Nentalea, Nentalea; Jalil, Abdul (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research is entitled "Arisan as Social Capital for Traders in the Central Market of Kendari City". The aim of this research is to find out and describe how social capital is in social gatherings between traders at the Kendari City Central Market and what forms of social gatherings exist between traders at the Kendari City Central Market. This research uses the theory of Trust by Francis Fukuyama regarding Social Capital. The research method used in this research is descriptive qualitative with an ethnographic approach to discover and comprehensively describe the cultural phenomena of a group.The results of this research show that traders in this market take part in various social gathering activities, containing social capital in this social gathering, namely in the treasurer and members of the social gathering. Where the treasurer is the main key in the running of the social gathering because this is closely related to the concept of social capital, one of which is trust. Then the forms of social gathering contained in this social gathering are only divided into two types of social gathering that they participate in, namely cash/money socializing and goods socializing. The social gathering between fellow traders in the form of cash/money also varies according to the nominal amount from tens of thousands to tens of millions and the social gathering for goods carried out by these traders is in the form of household furniture. The social gathering that takes place at the Kendari City Central Market has three types of social gathering, namely daily, weekly and monthly social gathering. Arisan not only functions as business capital, but arisan plays an important role in strengthening social networks between traders. With a social gathering, fellow traders can help each other with financial matters and also help build relationships of mutual trust and cooperation.